Scenarios for the future of the German confectionary market by 2030 - strategic implications for Ferrero Germany: sweet chaos narrative and strategy - Mendes, Rita Gomes (2023)
This work project explores the future of the German confectionery market employing the ‘Intuitive Logics School’ of scenario planning. The report focuses on extensive expert and client involvement, particularly collaborating with Ferrero Deutschland GmbH. The primary objective is to navigate high uncertainty, understand plausible events' impacts on industry, retail, and consumers, and dynamically respond to an unknown future. Developing a plausible scenario centered on the key uncertainties ‘Stability of Supply Chain’ and ‘Health Regulations’, contributes to fostering a heightened awareness. General strategic implications and specific strategic implications for the scenario, with action plans for Ferrero Deutschland GmbH.